1997
DOI: 10.1001/jama.1997.03540280056034
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia During Ambulatory Monitoring as a Prognostic Indicator in Patients With Stable Coronary Artery Disease

Abstract: Acute cardiac events in predominantly low-risk stable angina patients with confirmed coronary disease are unpredictable, and those more likely to suffer such an event cannot be identified by the detection of ambulatory ischemia. Acute nonfatal cardiac events result predominantly from the development of significant new coronary lesions, not initially severe enough to cause ischemia. Patients categorized as high risk for long-term medical therapy have an increased rate of cardiac events (mainly revascularization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…However, present data suggest that this is not necessarily the case in some patients under certain conditions. For example, studies using Holter recordings showed that a considerable number of patients with documented CAD frequently experience episodes of transient myocardial ischemia in their daily life (17). In such patients, transient enhancement of HRV provoked by inferior ischemia may often occur, leading to an erroneous interpretation of HRV.…”
Section: Discussionmentioning
confidence: 99%
“…However, present data suggest that this is not necessarily the case in some patients under certain conditions. For example, studies using Holter recordings showed that a considerable number of patients with documented CAD frequently experience episodes of transient myocardial ischemia in their daily life (17). In such patients, transient enhancement of HRV provoked by inferior ischemia may often occur, leading to an erroneous interpretation of HRV.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in low-risk or unselected patient cohorts failed to identify ambulatory ischemia as an adverse prognostic indicator during mid-or long-term follow-up. [67][68][69][70][71] Also, although one small study found the presence of ambulatory ischemia after coronary artery bypass graft surgery to be associated with a significant excess of adverse clinical events, 72 this finding was disproved by further larger studies. 73,74 The problem of small size, which plagued earlier investigations, was resolved with the publication during the 1990s of a number of studies [75][76][77][78][79][80] of sufficient magnitude and statistical power (300 to 1000 patients followed up over 1 to 3 years) to answer with confidence the question of the importance of silent ischemia on ambulatory monitoring.…”
Section: Patients With Anginamentioning
confidence: 99%
“…We found less than 50% narrowing in 48% of subsequent infarctions on serial angiography,2while in a study by Little et al the incidence was 66% 3. A recent angiographic study found progression of coronary disease on a second angiogram in 89% of patients with an acute syndrome and 74% of the lesions caused less than 50% stenosis on the first angiogram 4. Although these studies have selected out a population of patients in whom serial angiography was performed, the results differ significantly from patients who had been restudied and found to have a new total occlusion but without an intervening infarction.…”
Section: Pathophysiology Of Acute Coronary Syndromesmentioning
confidence: 46%